Evaluating the feasibility of oil palm agroforestry in Harapan Rainforest, Jambi, Indonesia - Rahmani, Tabah Arif; Nurrochmat, Dodik Ridho; Hero, Yulius; Park, Mi Sun; Boer, Rizaldi; Satria, Arif (Forestry Faculty, Universitas Hasanuddin, 2021)
About 2.5 million hectares of a total of 15 million hectares of oil palm plantation in Indonesia are planted in, or conflict with, the forest zone. Oil palm plantations face a conflict between socio-economic and ecological issues. This study was conducted in the Harapan Rainforest, Jambi to evaluate the potential of oil palm-based agroforestry to reconcile economic and ecological interests, by considering socio-economic and financial feasibility as well as biodiversity and land cover. The financial feasibility of oil palm agroforestry is compared to oil palm monoculture, employing a discounted cash flow approach using three indicators: net present value (NPV), benefit-cost ratio (BCR), and internal rate of return (IRR). Two ecological indicators—biodiversity and land cover—are evaluated in an experimental plot of oil palm agroforestry in Jambi. This study indicates that the NPV, BCR, and IRR of oil palm monoculture are IDR 62,644,836 (US 4,476.84), 1.39, and 20.77%, respectively, while the oil palm agroforestry planted in the experimental plot potentially generates much better values of financial indicators with NPV, BCR, and IRR being IDR 209,221,212 (US 14,951.76), 1.79, and 24.42%, respectively. Besides evaluating financial feasibility, we also found that the reviewed current studies indicate that the oil palm agroforestry provides positive ecological impacts, such as increased forest land cover, invertebrate fauna, and bird diversity.